Case report: Detection of anti-bullous pemphigoid antigen 180 antibodies in a patient with Behçet’s disease - Didona, Dario; Sequeira Santos, Antonio Manuel; Cunha, Tomas; Hinterseher, Julia; Kussini, Jacqueline; Hertl, Michael (Frontiers in Medicine, 2022)
Behçet’s disease (BD) is a systemic inflammatory disease of unknown etiology. BD is characterized by relapsing oral and genital ulcers, several different cutaneous lesions, relapsing bilateral uveitis, and other several manifestations, including vascular, gastrointestinal, neurological involvement. Serologically, BD is not characterized by disease-specific autoantibodies. Indeed, usually only laboratory markers of inflammation, such as C-reactive protein may be elevated in association with increased disease activity. Bullous pemphigoid (BP) is an autoimmune disease characterized by tense blisters and erosions, which can involve the oral mucosa in up to 20% of patients. Characteristically, BP patients shows serum IgG autoantibodies against BP180 and/or BP230. Tissue-bound autoantibodies can be visualized as a linear IgG and/or C3 staining along the basement membrane by direct immunofluorescence microscopy. Here, we firstly described a young patient with BD, who showed IgG autoantibodies against BP180 without developing blisters or urticarial-like plaques.